The Valley of Fear - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Valley of Fear" by Arthur Conan Doyle is a novel first published in 1915. In this fourth Sherlock Holmes mystery, the detective receives a coded warning about a plot against a country gentleman named Douglas. When Holmes arrives to investigate, he discovers Douglas has been murdered at his moated manor house. The case leads to dark secrets involving American coal miners, a corrupt trade union, and the dangerous Professor Moriarty. Holmes must unravel a mystery that spans two continents and threatens more lives. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Valley_of_Fear
Release date is 2002-06-01
Produced by David Brannan and David Widger
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Detective and mystery stories